Analisis Perjanjian Bilateral Indonesia Dengan Singapura: BITs Tentang Promosi Dan Perlindungan Industri Yang Ditandatangani Tahun 2018 Dan Berlaku Tahun 2021 - Friska Sitanggang (Jurnal Hukum dan Sosial Politik, 2023)
International bilateral agreements in the form of investment have an important role and significance in promoting development growth and economic progress. Through such agreements, the host country has the opportunity to attract foreign investors to operate and invest in various sectors in its territory. As a result, the home country can freely invest in various industrial sectors in the host country. The home country and the host country conclude an agreement in the form of international bilateral agreements called "investment promotion and protection agreements" or bilateral investment treaties/BITs. One such agreement is the international bilateral agreement between Indonesia and Singapore on industrial promotion and protection signed in 2018 and effective in 2021, which will be discussed in this journal.